INTERRELATION DEGREE OF SEVERITY PTERYGOPALATINE GANGLIONITIS WITH THE HYGIENIC CONDITION OF THE ORAL CAVITY - I.A. Kolisnyk (Ukrainian Medical Stomatological Academy, 2016)
Pterygopalatine ganglionitis is the most often among pathological syndromes of the face. Polymorphism of its manifestations significantly complicates diagnosis and choice of the optimal method of treatment, due to topographic, anatomical and functional features of the structure of peripheral vegetative nervous system of the head. Patients who suffer from ganglionitis often have worse oral hygiene. This is due to the presence of constant pain in the teeth-jaw system that reduces quality of life and focuses attention on the pain, and motivation to improve dental health in these patients is missing. The purpose of our study was to investigate the relationship status of oral hygiene, periodontal tissue and severity of pterygopalatine ganglionitis. We examined 93 patients with pterygopalatine ganglionitis aged 30 to 74 years. The control group consisted of 20 healthy patients aged 40 to 60 years. Nature of the pain attacks, its intensity, frequency and duration of occurrence, availability of the vegetative manifestation take into account at diagnosis. Objective criteria for diagnosis are: pain on palpation projection points out of cranial nerves, violations skin or mucosa sensitivity, positive symptom "skinfold". We used visual analog scale to assess pain intensity. The study of teeth, oral hygiene, periodontal tissues performed according to generally accepted scheme. To assess the hygienic condition the index Fedorov-Volodkina (1968) was used. The intensity of the inflammation of the tissues around the teeth evaluated using samples Schiller-Pisarev. The degree of damage of periodontal tissues was determined by papillary-marginally-alveolar index PMA by Parma (1960), periodontal index PI by Russel (1956). We allocated degrees of severity of pterygopalatine ganglionitis: easy, medium, hard in dependence on the intensity of pain, presence the vegetative symptoms, changes in skin sensitivity. CPR marked increase in the index, depending on the severity pterygopalatine ganglionitis that can explain the unreasonable removal of teeth with pain attacks. Also found significant violations of hygiene indexes, depending on the degrees of severity of pterygopalatine ganglionitis. Changes in periodontal tissues of patients indicate the presence of periodontal disease, and the severity of inflammatory changes amplified depending on the severity of the disease.